(untitled) (REMUNOM, 2026)
This study investigates the economic feasibility of investing in Distributed Photovoltaic Microgeneration (DPM) in Brazil by analyzing the influence of key variables, including the Current Acquisition Cost of Electric Energy (CAEEA), Taxes Related to the Bill (TRF), Interest Rate for Investments (TJI), Current Technology Level (NTA), and Solarimetry (SOL). A Central Composite Rotatable Design (CCRD) was employed to evaluate the effects of these independent variables on the economic indicators Discounted Payback (PBd) and Net Present Value (NPV). The methodology involved statistical regression analysis to model the relationships between the independent variables and the responses. Results indicated that CAEEA significantly impacted both PBd and NPV, with a higher CAEEA being desirable for DPM adoption. TRF and TJI also showed significant effects, with TRF positively influencing NPV, while TJI had an inverse impact. The most favorable conditions for promoting DPM were identified as CAEEA at R 1.57/kWh, TRF at 37.5%, TJI at 8.75% per annum, NTA at R 497.98/kWp, and SOL at 175.30 kWp/m². These findings suggest that increasing electricity costs, taxes, and technology levels, coupled with lower interest rates, can encourage investment in DPM, contributing to the diffusion of renewable energy sources in Brazil.